Mode of action exploration for prostate epithelial cell injury caused by bisphenol AChina Nucleotide Sequence Archive (CNSA) - Baofang Liang; Jinyao Chen; Liang Wang; Leyan Zhang; Shuzhen Huang; Yongru Zhou; Mengmei Ni; Lishi Zhang; Xiaohua Lv; Xiaomeng Li (Ecotoxicology and Environmental Safety, 2024)
Bisphenol A (BPA) is a typical food chemical contaminant with various detrimental effects, especially on reproductive system. Male prostate damage is also one of its major adverse health effects, of which mode of action (MOA) remains unclear. This study aims to explore the MOA for prostate toxicity of BPA using human normal prostate epithelial cell RWPE-1 for 28-day human-relevant-level exposure. A physiological based pharmacokinetic model was used to determine the concentration of BPA based on the actual oral exposure in China. The possible key events were identified by high-throughput transcriptome sequencing and validated by qPCR, Western blot and cell cycle assay, and the benchmark concentration analysis were conducted. The enriched KEGG pathways include the endocytosis, cell cycle, cellular senescence, MAPK and TNF signaling pathways. With increasing BPA concentrations, the increased mRNA and/or protein expressions of MAPKAPK2, c-JUN and c-fos in the MAPK signaling pathway, the increased mRNA expressions of CCND1 and CDKN1A, the decreased mRNA expression of CDC25C, the increased proportion of G0/G1 phase and S phase, as well as the decreased proportion of G2/M phase, were observed. The lowest value of benchmark concentration lower confidence limit (BMCL) was retrieved from G2/M phase ratio, with 110.580 and 175.862 nM for BMCL5 and BMCL10, respectively, much higher than the male gonad maximum concentration of 0.019 nM of BPA at the current exposure level of adult Chinese males. In conclusion, the MOA of BPA induced male prostatic toxicity at human-relevant levels may include: key event (KE)1-MAPK signaling pathway activation, KE2-disorder of cell cycle regulatory gene expression (increased expression of CCND1 and CDKN1A, decreased expression of CDC25C), and KE3-disturbance of cell cycle (increased proportion of G0/G1 and S phases, decreased proportion of G2/M phases). However, more studies are needed to validate and complete the MOA.